Moderne Kunst - Keuze uit het Frans Hals Museum. (Haarlem : Frans Hals Museum, 1970)
van Amen, Woody ; Alechinsky, Pierre ; Corneille ; Appel, Karel ; Moore, Henry ; Engelman, Martin ; Heyboer, Anton ; Fontana, Lucio ; Daniëls, Ger ; Breyten, Juan ; Clous, Rob ; Bazaine, Jean ; Hayter, William ; etc.
Moderne Kunst - Keuze uit het Frans Hals Museum, De Hallen - Grote Markt, Haarlem, 14 maart t/m 19 april 1970
boek